Amazing pleiotropic effects of azithromycin. Issue 4 (December 2018) - Lahousse, Lies
The AMAZES study was a large randomised, double-blind, placebo-controlled trial of azithromycin 500 mg given three times a week for 48 weeks in adults with persistent uncontrolled asthma to decrease asthma exacerbations and improve asthma-related quality of life [1]. The study was nationally funded in Australia and included 420 patients around the age of 60 years who were predominantly female (61%). Azithromycin reduced moderate-to-severe asthma exacerbations compared with placebo and significantly improved asthma-related quality of life. Only diarrhoea was significantly more frequent in users of azithromycin compared with placebo, although patients with hearing impairment or an abnormal prolongation of the corrected QT interval were excluded from the start of the study. The large randomised, double-blind, placebo-controlled AMAZES trial observed that azithromycin 500 mg given 3-times a week for 48 weeks in adults with persistent uncontrolled asthma decreased asthma exacerbations and improved asthma-related quality of life  http://ow.ly/WGlz30lLL7z